Alterations of Ion Homeostasis in Cancer Metastasis: Implications for Treatment - Fnu, Gulimirerouzi; Weber, Georg F. (Frontiers in Oncology, 2021)
We have previously reported that metastases are generally characterized by a core program of gene expression that induces the oxidative metabolism, activates vascularization/tissue remodeling, suppresses extracellular matrix interactions, and alters ion homeostasis. Among these features, the least elucidated component is ion homeostasis. Here we review the literature with the goal to infer a better mechanistic understanding of the progression-associated ionic alterations and identify the most promising drugs for treatment. Cancer metastasis is accompanied by skewing in calcium, zinc, copper, potassium, sodium and chloride homeostasis. Membrane potential changes and water uptake through Aquaporins may also play roles. Drug candidates to reverse these alterations are at various stages of testing, with some having entered clinical trials. Challenges to their utilization comprise differences among tumor types and the involvement of multiple ions in each case. Further, adverse effects may become a concern, as channel blockers, chelators, or supplemented ions will affect healthy and transformed cells alike.